Stimulasi Kecerdasan Majemuk Anak Usia Dini melalui Bermain Naturalistik - Anita Wardani; Naila Faizzatis Syifa; Khusnul Wahyu; Sulastri; Astutik (Mulya Literasi Publishing, 2026)
The purpose of this study is to describe the multiple intelligence of early childhood in naturalistic play spaces and identify hidden potentials that arise during play activities in RA Chairunnissa for the 2025/2026 Academic Year. Qualitative methods with phenomenological approaches are used in this study. The research subjects consisted of group B children and classroom teachers. Data collection techniques are carried out through participatory observation, semi-structured interviews, documentation in the form of children's works and photos of activities. Data was analyzed using an interactive analysis model that included data reduction, data presentation, and conclusion drawn. The validity of the data was obtained through triangulation techniques and source triangulation. The results of the study show that naturalistic play spaces are able to provide meaningful learning experiences and stimulate various children's multiple intelligences, especially naturalistic, kinesthetic, interpersonal, linguistic, and visual spatial intelligence. Children become more active, confident, communicative, creative, and able to show problem-solving skills through direct interaction with natural materials and outdoor play activities. Some children who appear passive in classroom learning show leadership, creativity, social sensitivity, and curiosity when in a naturalistic playroom. Thus, naturalistic playrooms can be an effective learning environment to uncover hidden potential and support early childhood development holistically.